2001
DOI: 10.1021/jf001393o
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Herbicidal Activity, and Mode of Action of IR 5790

Abstract: IR 5790, an arylthiadiazolone herbicide structurally related to oxadiargyl and oxadiazon, was synthesized. The herbicidal activity and mode of action of IR 5790 were investigated. This herbicide has broad-spectrum pre-emergence activity against both dicotyledonous and monocotyledonous weeds. The phenotypic responses of susceptible plants, such as interruption of growth and light-dependent development of necrotic areas on the foliage, are consistent with those observed with protoporphyrinogen oxidase-inhibiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…16 Pigment biosynthesis inhibitors are of great interest to organic chemists owing to their good selective toxicity and low use rate. 17 -22 In recent exploratory experiments by the present authors, bleaching was observed with novel pyrazoylpyrimidine compounds. Some compounds produced a chlorophyll level decrease in seedlings of Pennisetum alopecuroides L. and Brassica campestris L., causing progressive bleaching.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…16 Pigment biosynthesis inhibitors are of great interest to organic chemists owing to their good selective toxicity and low use rate. 17 -22 In recent exploratory experiments by the present authors, bleaching was observed with novel pyrazoylpyrimidine compounds. Some compounds produced a chlorophyll level decrease in seedlings of Pennisetum alopecuroides L. and Brassica campestris L., causing progressive bleaching.…”
Section: Introductionmentioning
confidence: 82%
“…Pigment biosynthesis inhibitors are of great interest to organic chemists owing to their good selective toxicity and low use rate . In recent exploratory experiments by the present authors, bleaching was observed with novel pyrazoylpyrimidine compounds.…”
Section: Introductionmentioning
confidence: 83%
“…Leaf disks from the three common waterhemp biotypes were prepared exactly as in the electrolyte leakage study and incubated in darkness at 25 C for 20 h. All extractions for high-performance liquid chromatography (HPLC) determinations of porphyrin were made under dim green light to prevent photodegradation of Proto. Common waterhemp leaf disks were homogenized in 2 ml of basic methanol (HPLC-grade methanol-0.1 N NH 4 OH [9:1 v/v]) with a homogenizer at full speed for 15 s and sonicated for 10 min as described previously (Dayan et al 2001). The supernatant was collected after centrifugation at 3,000 ϫ g for 3 min.…”
Section: Porphyrin Extraction and Quantitationmentioning
confidence: 99%
“…Therefore, PPO-inhibiting herbicides are of great interest due to their low use rates and environmentally benign characteristics. Since the 1970s, research on PPO inhibitors has been actively pursued, leading to two classes of commercial products, diphenyl ethers and N -phenyl phthalimides, the latter of which has become a very interesting research area . Structural optimization of the pioneering compounds of the N -phenyl phthalimides family, chlorphthalim and oxadiazon, as shown in Figure , resulted in the discovery of several commercial herbicides.…”
Section: Introductionmentioning
confidence: 99%